Impact of Adjuvant Radiotherapy for Malignant Salivary Gland Tumors. (December 2017) - Safdieh, Joseph; Givi, Babak; Osborn, Virginia; Lederman, Ariel; Schwartz, David; Schreiber, David
Objective: Using the National Cancer Database (NCDB), we investigated the characteristics, outcomes, and benefits of adjuvant therapy for patients diagnosed with malignant salivary gland tumors between 2004 and 2012. Study Design: Retrospective analysis. Setting: NCDB. Subject and Methods: The cases of patients diagnosed with a nonmetastatic major salivary gland tumor who underwent resection between 2004 and 2012 were abstracted from the NCDB. Patients were further included if they had pT1-4NX-1M0 high-grade disease or pT3-4NX-0M0 or pT1-4N1M0 low-grade disease. Patients were identified as having no postoperative radiation therapy or having received postoperative radiation therapy to a dose of 5000 and 7000 cGy to the head and neck region or the parotid region, and their characteristics and outcomes were compared. Results: During the study period, 4068 patients met the inclusion criteria for this analysis, of which 2728 (67.1%) received postoperative radiation and 1340 (32.9%) did not. With a median follow-up of 49.1 months, there was a significant improvement in overall survival associated with those receiving postoperative radiation (5 years, 56% vs 50.6%). On multivariable analysis, radiation utilization (hazard ratio, 0.78; 95% CI, 0.71-0.86; P < 0.001) and female sex (hazard ratio, 0.88) were associated with improved survival. When the analysis was limited to patients ≤65 years old, the survival benefit was persistent on multivariable analysis. Conclusion: In conclusion, in this large NCDB study of 4068 patients with locally advanced malignant salivary gland carcinoma, administering adjuvant radiotherapy was associated with improved overall survival.